Polypyrrole-doped conductive self-healing multifunctional composite hydrogels with a dual crosslinked network. Issue 36 (31st August 2021) - Wang, Xuemiao; Li, Xin; Zhao, Lingling; Li, Meng; Li, Yan; Yang, Wu; Ren, Jie
Abstract : Soft hydrogel materials can be applied for use in biosensors, wearable electronics, artificial skin, soft robots, and so on. Abstract : Soft hydrogel materials can be applied for use in biosensors, wearable electronics, artificial skin, soft robots, and so on. Practical applications require the materials to have various properties such as high conductivity, toughness, self-healing, stretchability, and so on. However, achieving all these features in a single material remains challenging at present. Herein, the fabrication of novel composite carboxymethylcellulose/poly(acrylic acid)/polypyrrole/Al(iii ) (CMC/PAA/PPy/Al(iii )) multifunctional hydrogels using a simple method is described. The mechanical and electrical self-healing properties are attained by multiple dynamic coordinations between Al 3+ ions and carboxyl groups from CMC and PAA together with the hydrogen bonding between PPy and the –OH of CMC and/or the −COOH of PAA. The electrical conductivity is achieved by the conductive polymer PPy, free ions, and the synergistic effect between the PPy particles and the free ions. Moreover, desirable mechanical properties, such as stretchability (1344%), toughness, and mouldability are realized by establishing a balance between the chemical and physical crosslinking networks, and the nanostructure of PPy. Thus, the resultant hydrogels have potential applications in electronic skin, biomedical implants, and wearable electronic devices in the future.